2016
DOI: 10.3892/ijmm.2016.2498
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with bone marrow mesenchymal stem cells combined with plumbagin alleviates spinal cord injury by affecting oxidative stress, inflammation, apoptotis and the activation of the Nrf2 pathway

Abstract: The aim of the present study was to investigate the protective effect exerted by bone marrow mesenchymal stem cells (BMSCs) in combination with plumbagin on spinal cord injury (SCI) and explore the mechanism behind this protective effect. Firstly, BMSCs were extracted from male Sprague-Dawley rats, cultured in vitro, and identified by hematoxylin. Sprague-Dawley rats were then randomly divided into a control group, SCI model group, BMSC-treated group, a plumbagin-treated group, and a BMSC and plumbagin-treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 41 publications
3
22
0
Order By: Relevance
“…As stem cell activities and differentiation capacities are important for MSC‐based therapeutic effects on repairing injury in vivo, drug treatments can also protect implanted MSCs from damage and then improve their biological activities for cell‐based treatments. The combination of bone marrow‐derived MSCs with plumbagin reduces the spinal cord water content after spinal cord injury by synergistically activating the Nrf2 pathway and regulating oxidative stress, inflammation and apoptosis in vivo . Injection of adipose‐derived MSCs and icariin markedly prevented apoptosis in transplanted MSCs and repaired erectile tissue structures in erectile dysfunction models, accompanied by increased levels of endothelial markers and smooth muscle markers in vivo …”
Section: Strategies To Control Ros Levels For Msc Fates In Vitro and mentioning
confidence: 99%
“…As stem cell activities and differentiation capacities are important for MSC‐based therapeutic effects on repairing injury in vivo, drug treatments can also protect implanted MSCs from damage and then improve their biological activities for cell‐based treatments. The combination of bone marrow‐derived MSCs with plumbagin reduces the spinal cord water content after spinal cord injury by synergistically activating the Nrf2 pathway and regulating oxidative stress, inflammation and apoptosis in vivo . Injection of adipose‐derived MSCs and icariin markedly prevented apoptosis in transplanted MSCs and repaired erectile tissue structures in erectile dysfunction models, accompanied by increased levels of endothelial markers and smooth muscle markers in vivo …”
Section: Strategies To Control Ros Levels For Msc Fates In Vitro and mentioning
confidence: 99%
“…Under treatment of SCI, some studies have shown that CoQ10 reduces the level of oxidative injury and antiapoptosis [19][20][21][22]. Medication combined with BMSC transplantation has been shown to have a powerful impact on protecting the vitality of cells and antioxidant and antiapoptotic compounds in SCI [23,24]. However, the method by which CoQ10 treatment can be combined with BMSC transplantation in SCI is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…4A and B). Since MSCs exert anti-inflammatory and immunomodulatory properties (3032), we next explored whether VPA+S1P priming can influence the anti-inflammatory effect of UC-MSCs. To address this issue, we prepared the CM collected from UC-MSCs unprimed, primed by VPA or S1P alone, and primed by VPA+S1P and examined whether CM could suppress the secretion of TNF-α from MH-S cells, an alveolar macrophage cell line, by stimulation with LPS (3).…”
Section: Resultsmentioning
confidence: 99%